The Garden - de Souza, Claudia; Andrade, Paula Simas de (Sustainability in Debate, 2014)
Following the motto “community and government, a partnership for success”, Sheila Souza dos Santos, 34, a secretary, transformed a community garden project into a true space for the exercise of citizenship. The revival of a community-based project for the production of garden vegetables in Itapoã ”“ a city located in the outskirts of Brasília, Brazil’s national capital ”“ resulted not only in access to healthier food by the local community, school and families engaged in the project, but also in a series of related community initiatives that involve children, teenagers, adults and senior citizens.